MOF‐derived Co/C‐anchored MoS2‐based phase change materials toward thermal management and microwave absorption - Yang Li; Xukang Han; Jiaying Zhu; Yuhao Feng; Panpan Liu; Xiao Chen (Electron)
Abstract With the miniaturization and integration of electronic devices, developing advanced multifunctional phase change materials (PCMs) integrating thermal storage, thermal conduction, and microwave absorption to address electromagnetic interference, thermal dissipation, and instantaneous thermal shock is imperative. Herein, we proposed an extensible strategy to synthesize MOF‐derived Co/C‐anchored MoS2‐based PCMs using high‐temperature carbonation of flower‐like MoS2 grown in situ by ZIF67 and vacuum impregnation of paraffin. The resulting MoS2@Co/C‐paraffin composite PCMs exhibited good thermal storage density, thermal cycling stability, and long‐term durability. The thermal conductivity of composite PCMs was 44% higher than that of pristine paraffin due to the construction of low interfacial thermal resistance. More attractively, our designed composite PCMs also possessed −57.15 dB minimum reflection loss at 9.2 GHz with a thickness of 3.0 mm, corresponding to an effective absorption bandwidth of 3.86 GHz. The excellent microwave absorption was attributed to the multicomponent synergy of magnetic loss from Co nanoparticles and conductive loss from MOF‐derived carbon layers, and multiple reflection of MoS2 nanowrinkle, along with good impedance matching. This study provided a meaningful reference for the widespread application of composite PCMs combining thermal storage, thermal conduction, and microwave absorption in high‐power miniaturized electronic devices.